Superfood in Malaysia: The butterfly pea flower (Clitoria ternatea L.) / Nur Atikah Mohamad Rizal and Hisham Mohd Nooh - Mohamad Rizal, Nur Atikah; Mohd Nooh, Hisham (2021)
Superfood is a term generally known as a type of food which provides many health benefits and well-being towards living things. It is a term closely related to functional food however the definition for superfood is indefinite as it is usually applied in advertising and marketing. Nevertheless, there are still many types of food that are related to the superfood term as they possess beneficial bioactive properties and high nutritional values. These foods are known throughout the world, but it is very hard to get here in Malaysia. Malaysia is a diverse country which comprises all sorts of food including edible flowers that possesses high nutritional values and bioactive properties. One of the famous known flowers is the butterfly pea flower or is called as Bunga Telang in Malaysia. Numerous researches have found that this flower consists of a high amount of bioactive properties and medicinal values but it is not regarded as a superfood. Hence, this review is to clearly identify the superfood term and to claim the butterfly pea flower as a type of superfood here in Malaysia. To accomplish this study, a review was carried out on topics relating to superfood and the butterfly pea flower. This study also includes the applications of the flower in food and the benefits it provides. Obtained findings on the general superfood properties were found to be synonymous with that of the flower which might consider the flower as a type of superfood.